Catalytic evaluation of Ru(II) and Co(II) salicylaldimine complexes for transfer hydrogenation of acetophenone - Ndou, Dakalo Lorraine (My University, 2017)
N-(aryl) salicylaldimine ligands were prepared by the condensation of salicylaldehyde and aniline, 2,6 – dimethylaniline, 2,6 – diisopropylaniline and N,N-diethyl-p-phenylenediamine to give the desired ligands in good yields (70 - 93 % yield). The synthesised ligands were characterised by NMR spectroscopy, FTIR spectroscopy, ESI mass spectrometry and elemental analysis. The purity of these ligands was determined by determining the meting points. Co(II) and Ru(II) complexes were prepared from Co(OAc)2.4H2O and [RuCl2(η6-p cymene)]2 to afford the N-(aryl) salicylaldiminato complexes Co1 – Co4 and Ru1 – Ru4 with yields in the range 60 – 66 % and 90 – 97 %, respectively. These complexes were characterised by NMR spectroscopy, FTIR, ESI mass spectrometry, elemental analysis and TGA. The purity of these complexes was also determined by determining the melting point. The transfer hydrogenation of acetophenone was studied using 2-propanol as the hydrogen source and KOH as the base with the Ru (II) and Co (II) complexes as catalyst precursors. The catalytic activity of these complexes was evaluated using 1H-NMR and GC - MS. Preliminary studies were performed for 6 h at 82 oC and the conversion was evaluated using 1H-NMR. Due to the low catalytic activity of these complexes, the reaction time was increased to 48 h. Increasing the reaction time resulted in improvements in the conversion of the complexes. The catalysis was also evaluated at various temperatures to study the effect it has on the activity of the complexes. Temperature was found to not have a significant effect on the conversion. The ruthenium complexes were found to be active towards the transfer hydrogenation of acetophenone but the cobalt complexes were observed to have no catalytic activity in the transfer hydrogenation of acetophenone. The ruthenium complexes were investigated in an ionic liquid – organic biphasic system with the aim of separating the metal complexes in order to reuse the catalysts. Toluene was the organic phase and [BMIM]BF4 was the ionic liquid which afforded a biphasic system. Three cycles were performed and the performance of Ru1 – Ru3 decreased with each cycle but Ru4 behaved differently as the performance increased with each cycle.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, University of the Witwatersrand, 2017
Keywords: Hydrogenation; Catalysis